(untitled) (LEARNing Landscapes, 2016)
This work o ers examples and discussion of the work of participants in a graduate- level education course where creative engagement and meaningful learning through artful inquiry were pursued in addressing the question, "Who are you as a scholarly professional?" We provide a brief description of the nature of coursework, followed by descriptions of participants’ work, and the authors’ experiences as graduate student and instructor in creating a Visual Journal and conducting the experience, respectively. There is a discussion of the motivations, challenges, and outcomes experienced by the authors as they seek to create meaningful and transformative learning experiences for themselves and others.